2017
DOI: 10.1007/s13178-017-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections Among Young Men Who Have Sex with Men: Experiences with Diagnosis, Treatment, and Reinfection

Abstract: Despite high rates of sexually transmitted infections (STIs) among young men who have sex with men (YMSM), little is known about their experiences with diagnosis, treatment, and reinfection. To fill this gap, we interviewed 17 YMSM ages 18-29 who participated in an online HIV prevention trial and tested positive for STIs at both the baseline and three-month follow-up assessments. Participants were asked about their reactions to testing positive, experiences with treatment, disclosure to partners, and changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Despite the appeal of the convenience of self-testing, we found three studies that identified issues with self-testing [ 28 , 29 , 30 ]. One study, conducted in the US, used a series of focus-group discussions with 21 young MSM of colour (aged 18–35 years) to explore the acceptability, preferences and usability of HIV self-test kits [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the appeal of the convenience of self-testing, we found three studies that identified issues with self-testing [ 28 , 29 , 30 ]. One study, conducted in the US, used a series of focus-group discussions with 21 young MSM of colour (aged 18–35 years) to explore the acceptability, preferences and usability of HIV self-test kits [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies suggested a previous negative experience of the testing process to be an important barrier to HIV/STI testing [ 28 , 31 , 32 , 33 , 34 , 35 ]. Common themes which emerged included feeling embarrassed during previous testing experiences and discomfort about discussing their sexual history.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations